Genetic studies on the inability of beta-galactosidase to be translocated across the Escherichia coli cytoplasmic membrane. - Lee, C (1989)
When a signal sequence is attached to beta-galactosidase, the normally cytoplasmic protein is unable to fully traverse the cytoplasmic membrane. We used a genetic approach to study those features of beta-galactosidase responsible for the block in translocation. By using both in vivo and in vitro techniques, fragments of beta-galactosidase were interposed between a signal sequence and alkaline phosphatase. The alkaline phosphatase acts as a sensor for any blocking effects of beta-galactosidase on export. From these studies, we show that multiple regions of beta-galactosidase contribute to its failure to be translocated. These results are most easily interpreted if the folding of beta-galactosidase or of domains of it is responsible for the block in export. In addition, in certain constructs, positively charged amino acids directly following the signal sequence interfered with export.